PROJECT-BASED LEARNING DALAM PEMBELAJARAN BAHASA INGGRIS PADA PROGRAM STUDI PARIWISATA - Made Novita Dwi Lestari; I Putu Edi Sutrisna (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2022)
Learning English, especially in the tourism study program, is very important to emphasize. However, the process of learning English in fact still faces various obstacles. One of the obstacles that are often faced in the process of learning English is that lecturers tend to apply a one-way learning process from lecturer to student using the lecture method. For this reason, it is necessary to further analyze the model or learning approach that is more possible and has the potential to effectively assist students in the English learning process. One model of English learning that has the potential to effectively help students in tourism study programs is to apply a project-based learning model. Therefore, the present study utilizes a qualitative descriptive approach using library research methods aiming at analyzing the concept of project-based learning to be implemented in English learning environments in tourism study programs.  This library research approach, according to Lin (2009) involves reading and categorizing materials to solve a problem. Thus, from the result of the study it was found that the use of project-based learning in learning English in the tourism study program is assumed to be able to help students prepare for the future well in terms of English skills and at the same time help lecturers to prepare a more meaningful English learning process.